First record of Amphipoda Talitroides topitotum (Burt, 1934) (Gammaridea, Talitridae) in the State of Espírito Santo, Brazil - doi: 10.4025/actascibiolsci.v35i1.12447 - Eutrópio, Frederico Jacob (2012)
Talitroides topitotum (Amphipoda) was introduced in Brazil by silviculture activities. Currently the species is distributed in the states of Paraná, Rio de Janeiro and São Paulo. This paper describes the species’ occurrence in the state of Espírito Santo. The objective of this study was to determine the interference of the edge effect on community structure of macroinvertebrates associated with leaf litter, where a T. topitotum female specimen was observed in coffee cultivations in March 2008.